Deteksi Relief Candi Borobudur Menggunakan Metode Template Matching - Anggotra, Puspadevi; Muliantara, Agus (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
Borobudur Temple has an area of ??about 2500 square meters, with a length of 121.66 meters, a width of 121.38 meters, and a height of 35.40 meters. This colossal building is also decorated with 2,672 relief panels and 504 Buddha statues. The large number of reliefs makes people often do not know information about these reliefs. Even though each relief itself actually has many stories of its own. Due to these problems, it is necessary to have a relief detector that can help tourists to find out more information about these reliefs. In this study, the authors use template matching with the Minimum Square Difference and Normalized Cosine Coefficient methods to identify relief. The stage for relief detection starts from the preprocessing stage and then performs template matching using 2 different methods. The test results from 23 images obtained the percentage of success of the system using the Normalized Cosine Coefficient method 34,78% and Minimum Square Difference method is 82.60%.